Impact of Agro-industrial Byproducts on Bioconversion, Chemical Composition, in vitro Digestibility, and Microbiota of the Black Soldier Fly (Diptera: Stratiomyidae) Larvae. Issue 1 (22nd January 2021) - Galassi, Gianluca; Jucker, Costanza; Parma, Pietro; Lupi, Daniela; Crovetto, Gianni Matteo; Savoldelli, Sara; Colombini, Stefania
Abstract: The interest in using byproducts from agro-food industries as a rearing substrate for insects is increasing rapidly. We investigated the influence of byproducts of vegetal origin (okara—a byproduct of soy milk production, maize distillers with solubles, brewer's grains), used as rearing diet for black soldier fly larvae (BSFL), on the following parameters: biomass production, substrate reduction (SR), nutritional profile and in vitro digestibility, and larval gut microbiota. Hen diet was used as a control substrate. The highest larval biomass was collected on maize distillers, whereas the highest SR was observed on okara. The rearing substrate affected ash, ether extract, and chitin larval content. The BSFL reared on okara were characterized by a lower lauric acid content (17.6% of total fatty acids). Diets also influenced in vitro crude protein digestibility (%) for monogastrics, with the highest values for BSFL reared on maize distillers (87.8), intermediate for brewer's grains and okara BSFL, and the lowest for hen BSFL (82.7). The nutritive value for ruminants showed a lower Net Energy for lactation for BSFL reared on hen diet than okara and dried maize distillers BSFL. The different byproducts showed an influence on the larval gut microbiota, with a major bacterial complexity observed on larvae fed with the hen diet. The neutral detergent fiber concentration of dietary substrate was negatively correlated with Firmicutes and Actinobacteria relative abundance. Insects valorized byproducts converting them into high-value larval biomass to be used for feed production. The results evidenced the effects of the tested byproducts on the measured parameters, underling the chemical composition importance on the final insect meal quality.